2014
DOI: 10.1186/preaccept-6398159631419553
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the anthelmintic activity of medicinal plant extracts and purified condensed tannins against free-living and parasitic stages of Oesophagostomum dentatum

Abstract: Background: Plant-derived condensed tannins (CT) show promise as a complementary option to treat gastrointestinal helminth infections, thus reducing reliance on synthetic anthelmintic drugs. Most studies on the anthelmintic effects of CT have been conducted on parasites of ruminant livestock. Oesophagostomum dentatum is an economically important parasite of pigs, as well as serving as a useful laboratory model of helminth parasites due to the ability to culture it in vitro for long periods through several life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…Indeed, a recent report has indicated that increased proportions of A-type linkages may enhance the in vitro activity of PAC against E. coli 32 . The potent, lethal effect of the extract tested here against A. suum indicated the presence of other compounds with superior anthelmintic activity to the range of PAC molecules which have been tested previously against a multitude of helminths including A. suum , O. dentatum 33 , Ostertagia ostertagi 34 and Haemonchus contortus 35 . This rapid lethality also contrasted to our previous experiments with A. suum larvae where incubation in other tested plant extracts, or synthetic anthelmintic drugs such as ivermectin, resulted in impaired motility and migratory ability but generally larvae remained alive (data not shown).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Indeed, a recent report has indicated that increased proportions of A-type linkages may enhance the in vitro activity of PAC against E. coli 32 . The potent, lethal effect of the extract tested here against A. suum indicated the presence of other compounds with superior anthelmintic activity to the range of PAC molecules which have been tested previously against a multitude of helminths including A. suum , O. dentatum 33 , Ostertagia ostertagi 34 and Haemonchus contortus 35 . This rapid lethality also contrasted to our previous experiments with A. suum larvae where incubation in other tested plant extracts, or synthetic anthelmintic drugs such as ivermectin, resulted in impaired motility and migratory ability but generally larvae remained alive (data not shown).…”
Section: Discussionmentioning
confidence: 65%
“…All assays included media only, as a negative control, and ivermectin (50 μg/mL) as a positive control. O. dentatum L3 survival was also assessed by an agar-based migration inhibition assay 33 . The number of migrating worms was used as a surrogate measure for the number of live worms, as we have observed with O. dentatum in this assay that close to 100% of viable worms are able to migrate.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism(s) of the observed synergistic actions are not yet known. Tannins have been shown to deform nematode surfaces ( Hoste et al., 2006; Williams et al., 2014a, b ). Interestingly, exposure to extracts from tannin-containing plants (which would also have contained flavonoids) caused degeneration of muscle cells, accumulation of electron-dense vesicles and marked intracellular disorganisation ( Brunet et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such contrasting CT fractions are needed to give an insight into which structural features should be targeted by plant selection or breeding before recommending these bioactive compounds in livestock feeds. It has previously been reported that larger CT polymers in comparison with smaller ones more efficiently inhibit the feeding ability of first-stage larvae (L1) of Ostertagia ostertagi and Cooperia oncophora in cattle (Novobilský et al 2013 ), and also the motility of L4 of A. suum and Oesophagostomum dentatum in pigs (Williams et al 2014 a , b ). However, CT extracts and fractions tend to vary in terms of tannin contents and composition, which can complicate the interpretation of results compared to using pure compounds, e.g.…”
Section: Introductionmentioning
confidence: 99%